Prospective multicentre randomised controlled trial of the effect of Braun Enteroenterostomy in the Reconstruction after Pancreaticoduodenectomy on delayed gastric emptying (DGE): protocol for the BERP study. Issue 12 (12th December 2022) - Gupta, Saksham; Brown, Kai; Lott, Natalie; Carroll, Rosemary; Burnett, David; Nikfarjam, Mehrdad
Abstract : Introduction: Despite advances in achieving low mortality rates with pancreaticoduodenectomy (PD), morbidity remains high. A key contributor to this morbidity is delayed gastric emptying (DGE) occurring with an incidence of up to 30%. The utility of a Braun enteroenterostomy (BE) appears promising to reducing the incidence of DGE, but current research is not definitive. Methods and analysis: This project will be designed as a prospective multicentre randomised controlled blinded study to assess how BE effects the rate of DGE after PD in the setting of malignancy, within Australia—with blinding of patients, outcome assessors and data analysts. Patients will be randomly assigned to PD with Billroth II reconstruction with BE versus PD with Billroth II reconstruction without BE. The primary outcome is the incidence of DGE as defined by the International Study Group of Pancreatic Surgery. Secondary outcomes will include length of hospital stay, postoperative pancreatic fistula incidence, development of major complications (Clavien-Dindo≥3 a), quality of life and 90-day mortality. The study will be powered at 80% to detect a reduction in DGE rate from 30% to 15%, requiring a total of 264 study participants. An interim analysis will be performed once a total of 104 study participants have been recruited at which point the study will be able to detect reduction in DGE from 30% to 10% with 80% power. Statistical analysis will be done with intention-to-treat principles. The proportion of patients suffering DGE will be compared between treatment arms using a χ 2 test, with p values used to represent statistical significance. Ethics and dissemination: The study has been ethically approved by the Hunter New England Human Research Ethics Committee (2021/ETH11939), with results disseminated through presentation and publication. Trial registration number: CTRN12622000048785.